2022
DOI: 10.32764/schoolar.v1i4.1322
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Patterns of Teachers and Students in Islamic Religion Education lesson on Online Class at Plandaan Senior High School Jombang

Abstract: In the Covid 19 era, learning became online, so the learning process was carried out online. The objectives of the researcher are: 1) Knowing the pattern of interaction between teachers and students, during online learning 2.) Knowing the supporting and inhibiting factors during the online learning process 3.) Overcoming obstacles during the online learning process. This study uses a qualitative descriptive method which is applied at SMA Negeri Plandaan Jombang class XI Mapel PAI which consists of 30 students.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…From these results, it can be same with Rohmah & Anggraini (2021) findings that showed the classroom interaction relied heavily on the teachers. Moreover, based on the observation, the passiveness of the students caused it.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…From these results, it can be same with Rohmah & Anggraini (2021) findings that showed the classroom interaction relied heavily on the teachers. Moreover, based on the observation, the passiveness of the students caused it.…”
Section: Discussionsupporting
confidence: 86%
“…Those results show that the 'Teacher Talks' category dominates the interactions in the classroom. This finding is relevant to Rohmah & Anggraini (2021) research that showed the Teacher dominates all the interactions in the classroom which make it the Class Teacher-Centered.…”
Section: %mentioning
confidence: 67%
“…In order to make Nahwu learning more effective, the teaching material book should link learning with contextual concepts, in other words, teaching material books should be related to environmental conditions and events experienced by students so that it is easier to understand the material. Learning by using teaching materials with a contextual approach will involve the active role of students in the environment so that it can make learning meaningful for students (Rohmah & Pratama, 2022). A background contextual approach to students learning through activities that they experience themselves in the environment and not just knowing, remembering, and understanding the subject matter.…”
Section: Introductionmentioning
confidence: 99%